A novel design of bi-directional silica-based erbium-doped fibre amplifier for broadband WDM transmissions - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Poopalan, P.; Selvakennedy, S.; Ahmad, Harith (Elsevier, 2001)
A new method for a broadband amplification based on erbium-doped fibre amplifier was developed using only a single laser diode pumped at 1480 nm. A dual-stage amplifier was employed where the first stage provides simultaneous bi-directional amplification of conventional- and long-band signals. The utilisation of unused amplified spontaneous emission and remnant pump power from the first stage enables realisation of high gain for the long-band signals in the second stage. Amplification of wavelength division multiplexing systems (two and four channels) was successfully demonstrated with an average gain of 22 dB and a noise figure less than 7 dB. (C) 2001 Elsevier Science B.V. All rights reserved.